2004
DOI: 10.1002/adsc.200303203
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine Reagents for the Oxidation of Alcohols and Their Application to Complex Molecule Synthesis

Abstract: Hypervalent iodine(V) derivatives such as 2-iodoxybenzoic acid (IBX) and Dess±Martin periodinane [DMP; 1,1,1-tris(acetyloxy)-1,1-dihydro-1,2-benziodoxol-3-(1H)-one] have been used widely for the oxidation of alcohols to aldehydes and ketones during the last decade because of their high chemoselectivity, mild reactivity, and high yielding process. This review focuses on the recent progress in the oxidation of alcohols to carbonyl compounds using IBX, DMP, and other hypervalent iodine reagents, and their applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 337 publications
(58 citation statements)
references
References 111 publications
1
51
0
2
Order By: Relevance
“…In 1996, Zhdankin8 reported that the reaction of simple hydrocarbons with azidoiodane 1 in the presence of benzoyl peroxide led to the selective azidation of 3° and activated 2° C–H bonds in moderate to good yield 911. Hartwig recently discovered that Fe/PyBOX catalysts promote aliphatic C–H azidation with 1 under milder conditions, allowing the labeling of complex natural products with high selectivity 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Zhdankin8 reported that the reaction of simple hydrocarbons with azidoiodane 1 in the presence of benzoyl peroxide led to the selective azidation of 3° and activated 2° C–H bonds in moderate to good yield 911. Hartwig recently discovered that Fe/PyBOX catalysts promote aliphatic C–H azidation with 1 under milder conditions, allowing the labeling of complex natural products with high selectivity 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…[2b] Am ajor reason for this side reaction is the difficulty associated with the tunable reactivity of phenols by controlling their oxidation potential using aprotecting group for the phenol hydroxy group.T herefore,t he development of an efficient catalytic cross-coupling of unprotected phenols for the construction of biaryl compounds is still highly desirable.R ecently,W aldvogel and co-workers reported an electrochemical phenolarene cross-coupling reaction using boron-doped diamond electrodes. [10][11][12][13][14][15] Inspired by these studies,wenow report abroadly applicable organoiodine(III)-catalyzed oxidative cross-coupling reaction of phenols using Oxone as aterminal oxidant (Scheme 1). [9] While recent metal-catalyzed cross-couplings of phenols have been studied, the organocatalytic cross-coupling reaction still remains particularly challenging.R ecently,w e developed the oxidative cross-coupling reaction of aromatic compounds using hypervalent iodine reagents.…”
mentioning
confidence: 99%
“…LiTMP was used as the base to generate the corresponding benzyne, 20 and acetaldehyde enolate was produced in situ from n -BuLi and THF. While previous studies took acetaldehyde enolate as the limiting reagent, 17, 18 we found higher yield of benzocyclobutenol 7a was obtained when aryl bromide 6a was used as the limiting reagent (entry 2).…”
Section: Resultsmentioning
confidence: 99%